Mercury increases IL-1β and IL-18 secretion and intensifies coronary arteritis in an animal model of Kawasaki disease - Alphonse, Martin P.; Duong, Trang T.; Tam, Suzanne; Yeung, Rae S. M. (Frontiers in Immunology, 2023)
Kawasaki disease (KD) is a multisystem vasculitis that predominantly targets the coronary arteries in young children. Epidemiological data suggest both environmental and genetic factors contribute to the susceptibility and severity of the disease. Mercury (Hg) is a known environmental pollutant and a Ca2+ signaling modulator. Ca2+ signaling regulates the activation of NLRP3 inflammasome. Using the Lactobacillus casei cell wall extract (LCWE) induced coronary arteritis mouse model of KD; we studied the effect of mercury on inflammasome activation and its impact on the immunopathogenesis of KD. Mercury enhances the expression of inflammasome activation resulting in caspase-1 mediated secretion of IL-1β and IL-18 cytokines. In vivo, the administration of mercury together with disease inducing LCWE exacerbates disease resulting in increased incidence and severity of coronary arteritis compared to LCWE alone. Mercury can act as a novel danger signal modulating Ca2+ signaling to increase IL-1and IL-18 secretion and intensifies coronary arteritis in an animal model of KD.